In vivo antitumour potential of camel’s milk against hepatocellular carcinoma in rats and its improvement of cisplatin renal side effects - Hala M. F. El Miniawy; Kawkab A. Ahmed; Sameeh A. Mansour; Marwa M. Salah Khattab (Pharmaceutical Biology, 2017)
Context: Camel milk (CM) is recommended for liver disease patients in Egypt for a strong belief that it has a curative effect. Objective: The effect of consumption of CM with or without chemotherapeutic drug cisplatin was evaluated on induced hepatocarcinogenesis in rats. Materials and methods: Wistar male rats (56) were divided into eight groups (7 rats each). Group I was control. Hepatocarcinogenesis was initiated by a single dose of intraperitoneal injection of diethylnitrosamine (DENA) (200 mg/kg BW) and promoted by phenobarbitone (500 ppm) in drinking water in groups V, VI, VII and VIII. Treatment started from 28th till 38th week using CM (5 mL/day) and/or cisplatin (5 mg/kg/3 weeks) in groups II, III IV, VI, VII and VIII. Biochemical analysis, lipid peroxidation and superoxide dismutase (SOD) activity in liver tissue were performed. Histopathology of liver and kidney and immunohistochemistry of placental glutathione-S-transferase (P-GST) in liver were performed and analyzed using image analysis. Results: Albumin concentration and SOD activity were 3.13 ± 0.23 and 311.45 ± 41.71 in group VII (DENA & cisplatin), whereas they were 4.3 ± 0.15 and 540.5 ± 29.94 in group VII (DENA, CM and cisplatin). The mean area of altered hepatocellular foci and P-GST altered foci decreased in group VI (DENA and CM) (1049.6 ± 174.78 and 829.1 ± 261) and group VIII (cisplatin and CM) (1615.12 ± 436 and 543.9 ± 127) compared to group V (DENA only) (4173.74 ± 510.7 and 3169.49 ± 538.61). Cisplatin caused chronic interstitial nephritis, which was slightly alleviated in group VIII (CM and cisplatin). Conclusions: CM had an antioxidant effect and together with cisplatin managed to decrease hepatocarcinogenesis.